2009
DOI: 10.1158/1535-7163.mct-08-0755
|View full text |Cite
|
Sign up to set email alerts
|

Consensus transcriptome signature of perineural invasion in pancreatic carcinoma

Abstract: Perineural invasion, the growth of tumor cells along nerves, is a key feature of pancreatic cancer. The cardinal symptom of pancreatic cancer, abdominal pain often radiating to the back, as well as the high frequency of local tumor recurrence following resection are both attributed to the unique ability of pancreatic tumor cells to invade the neuronal system. The molecular mechanisms underlying the neuroaffinity of pancreatic tumors are not completely understood. In this study, we developed a novel method to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 27 publications
6
67
0
Order By: Relevance
“…MAPRE2 up-regulation was evident in the nerve invasive clones of all three pancreatic cancer cell lines (Fig. 1A), confirming our micro-array data (6). Although expression of these genes in all NP clones was not significantly different, the tendency of MAPRE2 up-regulation from NP0 to NP3 was obvious.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…MAPRE2 up-regulation was evident in the nerve invasive clones of all three pancreatic cancer cell lines (Fig. 1A), confirming our micro-array data (6). Although expression of these genes in all NP clones was not significantly different, the tendency of MAPRE2 up-regulation from NP0 to NP3 was obvious.…”
Section: Resultssupporting
confidence: 85%
“…Previously (6) and in the present study we have identified MAPRE2 as a potential factor in perineural invasion of pancreatic cancer cells. MAPRE2 levels were increased in the three established highly nerve invasive pancreatic cancer cell clones in comparison to the respective parental cells.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations